(untitled) (Nigerian Journal of Technology, 2023)
This work presents the nonlinear analysis of the dynamics of large strain deformation of subsea flowlines and jumpers conveying two-phase fluid. Precisely, flexible pipes operating in the stated condition undergo large strain deformations. Thus, the known nonlinear deterministic model of the system is solved using method of discretized perturbation. Precisely, this study obtained the nonlinear natural frequency of simply supported flexible pipes modelled using the large strain deformation theory. Results show that both hardening and softening nonlinear behaviors are indicated for pipe undergoing large strain deformation compared with deformations modelled with small strain theory. Thus, operational insights and parameters for sustainable management of large strain deformed subsea flow lines and jumpers conveying two phase flow are made available.